Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Solutions to differential equations

  1. Apr 1, 2013 #1
    y(x)=A*e^(λx) ; y'=λy

    attempt at solution:

    y'(x)= Ae^(λx)*λ

    λy= Ae^(λx)*λ

    divide by λ, which cancel. then i get:

    y=Ae^(λx)

    i want to say the differential equation holds but the issue i see is that y' and y'(x) are not equal derivatives, so my final answer is that the differential equation does not hold. what do you guys think?
     
  2. jcsd
  3. Apr 1, 2013 #2
    $$ y=\text{Ae}^{\text{$\lambda $x}}\text{ } $$
     
  4. Apr 1, 2013 #3
    Latex accident! Will repost later today :)
     
  5. Apr 1, 2013 #4

    HallsofIvy

    User Avatar
    Staff Emeritus
    Science Advisor

    So you want to show that [itex]y(x)= Ae^{\lambda x}[/itex] is the general solution to the differential equation [itex]y'= \lambda y[/itex] or that it is a solution? The first is harder than the second! I don't understand what you mean when you say " y' and y'(x) are not equal derivatives". They are just slightly different ways of writing exactly the same thing- the first just doesn't have the "(x)" which is assumed since y is a function of x.

    But your "proof" is a little over complicated. All you need is

    If [itex]y= Ae^{\lambda x}[/itex] then [itex]y'= A\lambda e^{\lambda x}= \lambda (A e^{\lambda x})= \lambda y[/itex].
     
  6. Apr 1, 2013 #5
    when i say y' im referring to the equation y'=λy and also refferring to y'(x)=Ae^(λx)*x in my example. i know they are both the same. Do the two equations i listed above look equal to eachother?
     
  7. Apr 1, 2013 #6

    Mark44

    Staff: Mentor

    There's a typo here. I think you mean y'(x) = Aλeλx.
    Equations are not "equal" to each other. Equations can be equivalent, which means they have the same set of solutions.

    For your differential equation y' = λy, it can be shown that all solutions are of the form y = Aeλx. If you differentiate the latter equation, you get y' = Aλeλx = λy.
     
  8. Apr 1, 2013 #7

    So in this case I can set y' and y'(x) equal to each other even though when I take the derivative of y(x) i get y'(x)=Ae^(λx)*λ which does not equal y' = λy? Again I did set them equal to each other and got the original y(x). So this is a solution to a diff eq.
     
  9. Apr 1, 2013 #8

    HallsofIvy

    User Avatar
    Staff Emeritus
    Science Advisor

    You've got me really confused. If [itex]y= Ae^{\lambda x}[/itex] then [itex]y'= A\lambda e^{\lambda x}= \lambda(Ae^{\lambda x})= \lambda y[/itex] They are exactly the same!
     
    Last edited: Apr 1, 2013
  10. Apr 1, 2013 #9
    Thanks I wasn't thinking never mind. Thanks for the clarification.
     
Know someone interested in this topic? Share this thread via Reddit, Google+, Twitter, or Facebook